Estimating the added mass and the active drag force during push-off in flip turns - Pereira, S. M.; Silva, S. G.; Gonçalves, P.; Fernandes, R. J.; Machado, L.; Roesler, H.; Vilas-Boas, J. P. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
INTRODUCTION: While swimming, the swimmer moves his/her water, setting it into motion. The same occurs at the flip turns, however the swimmer is now contacting the wall. We may thus register the force applied by the swimmer by placing an underwater force platform at the wall. If we simultaneously video record the turns, we have also access to the position of its center of mass. Similarly to Lyttle et al. (1999), we have merged video and force data in order to estimate the active drag force and the added mass during flip turns. The study of the force production in the flip turns has also been studied numerically by Klauck (2005). Lyttle et al. (1999) used the F=m.a law, obtaining the acceleration from a 2nd order derivative, a numerically unstable procedure; we used the I=m(Vf-Vi) law, obtaining the velocity from a first numerical derivative (numerically unstable) and the impulse by an integration of the force (a numerically stable procedure). METHODS: An extensometric underwater force platform, two above water and four underwater fixed cameras (50Hz) were used, all synchronised. With a sample of 10 swimmers, six males and four females, all participants at the Absolute Portuguese National Championships, 89 valid turns were analysed. Using the APAS software to analyze the video and a MATLAB routine to analyze data from the force plate and combine it with the kinematic data, it was possible to estimate the active drag force and the total mass (swimmer mass + added mass) during contact time. RESULTS: The results (mean ± SD) obtained for the total sample were 0.5 ± 0.14 N/BW, 1.10 ± 0.22 N/BW, 1.58 ± 0.30 kg/BM and 2.38 ± 0.77 kg/BM, for the mean and maximum active drag force, and the mean and maximum total mass, respectively. DISCUSSION: From the results it is possible to conclude that during the flip turns the swimmer moves itself plus over its body mass of water on average, while the peak values may exceed three times its body mass. Putting all this water in motion adds to the drag force experienced by the swimmer. The results suggest that this method is suitable to compute the drag force and the added mass during flip turns.